Possible Involvement of Akt Activity in Endothelial Dysfunction in Type 2 Diabetic Mice - Yasuhiro Takenouchi; Tsuneo Kobayashi; Takayuki Matsumoto; Katsuo Kamata (Elsevier, 2008)
We investigated the effects of chronic simvastatin treatment on the impaired endothelium-dependent relaxation seen in aortas from type 2 diabetic mice. Starting at 8 weeks of diabetes, simvastatin (10 mg/kg per day) was administered to diabetic mice for 4 weeks. The significantly elevated systolic blood pressure in diabetic mice was normalized by simvastatin. Aortas from diabetic mice, but not those from simvastatin-treated diabetic mice, showed impaired endothelium-dependent relaxation in response to both clonidine and adrenomedullin. After preincubation with an Akt inhibitor, these relaxations were not significantly different among the three Akt inhibitor-treated groups (controls, diabetics, and simvastatin-treated diabetics). Although clonidine-induced NOx−(NO2−+NO3−) production was greatly attenuated in our diabetic model, it was normalized by simvastatin treatment. The expression levels of both total Akt protein and clonidine-induced Ser-473-phosphorylated Akt were significantly decreased in diabetic aortas, while chronic simvastatin administration improved these decreased levels. The expression level of clonidine-induced phosphorylated PTEN (phosphatase and tensin homolog deleted on chromosome ten) was significantly increased in diabetic aortas, but chronic simvastatin did not affect it. These results strongly suggest that simvastatin improves the endothelial dysfunction seen in type 2 diabetic mice via increases in Akt and Akt phosphorylation. Keywords:: diabetes, endothelial cell, statin, Akt, phosphatase and tensin homolog deleted on chromosome ten (PTEN)